ChemInform Abstract: Employing Carboxylic Acids in Aryne Multicomponent Coupling Triggered by Aziridines/Azetidines. Issue 18 (April 2016) - Roy, Tony; Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Thangaraj, Manikandan; Garai, Bikash; Biju, Akkattu T.
Abstract: The aryne multicomponent coupling involving carboxylic acids initiated by aziridines as nucleophiles affords N‐aryl β‐amino alcohol derivatives while the application of azetidines as nucleophilic triggers furnishes N‐aryl γ‐amino alcohol derivatives.